Ghanaian Chinese Language Learners’ Perception of Chinese Characters - Bright Nkrumah; Raymond Asamoah (Universitas Muhammadiyah Yogyakarta, 2022)
This paper investigated students’ perception of learning Chinese characters at the University of Ghana. The Chinese writing system is an exclusive indispensable script that forms part of the Chinese culture. However, the complexity, forms, strokes, pronunciation, radicals, and orthography structure of the characters makes it difficult for Ghanaian students to learn the Chinese language. A qualitative and quantitative design was used for the study. Of 338 students, 183 participated in the study from the first to the fourth year. Purposive sampling was used to select the students to respond to the questionnaire and share their opinions about the Chinese characters in interviews. The findings showed that (a) reading and writing of the Chinese characters were perceived to be more difficult than speaking. (b) the Chinese character radicals, forms, remembering of strokes, orders, numbers, and the orthography structure of the Chinese characters were a hurdle for Chinese language learners. Suggestions were made to urge students to cultivate the habit of consistently practicing the characters through collective participation and learning. The language learners need to do away with excuses, fear, and make-believe obstructions and spend more time in the learning process to enhance their skills in the Chinese writing system.